The Transcriptional Repressor CC2D1A/Freud-1 Interacts with the Chromatin Remodeling Protein Brg1 - Mirédin, Kim (Université d'Ottawa / University of Ottawa, 2012)
The serotonin-1A (5-HT1A) receptor plays an important role in the regulation of the serotonin (5-HT) system as an autoreceptor on 5-HT neurons. The transcription factor CC2D1A/Freud-1 is a potent repressor of the 5-HT1A promoter in neuronal but not in non-neuronal cells. The clinical relevance of Freud-1 is evident in a naturally occurring mutation, resulting in a truncated form of Freud-1 lacking its C-terminal half, that is associated with non syndromic mental retardation in humans. Thus, it is of interest to clarify the structure and function of Freud-1. As Freud-1 was shown to interact with the transcriptional regulator Brg1 at the 5-HT1A promoter, identification of the structural domains mediating the Brg1/Freud-1 interaction is required to assess the role of Brg1 in Freud-1 repression. In this study, I used pull-down assays with recombinant proteins, co-immunoprecipitation studies and immunofluorescent staining with confocal microscopy to show that Freud-1 interacts directly with the C-terminus of Brg1 and that the C-terminal domain of Freud-1 is required for this interaction.
Keywords: CC2D1A; Freud-1